Whole-brain radiation therapy plus simultaneous integrated boost for brain metastases from breast cancers - Zhang,Hongyan; Wu,Qiuji; Li,Li; Wang,Linwei; Zhong,Yahua (PeerJ, 2024)
Background The effect of whole-brain radiation therapy (WBRT) plus simultaneous integrated boost (SIB) in brain metastasis from breast cancers has not been demonstrated. Method In this single-center retrospective study, we reviewed consecutive breast cancer patients who developed brain metastasis and were treated with hypofractionated radiation therapy plus WBRT using intensity-modulated radiation therapy (IMRT)-SIB approaches. We analyzed clinical outcomes, prognostic factors and patterns of treatment failure. Result A total of 27 patients were eligible for analysis. Four (14.8%) patients achieved clinical complete response and 14 (51.9%) had partial response of brain lesions. The other nine patients were not evaluated for brain tumor response. The median brain progression-free survival was 8.60 (95% CI [6.43–13.33]) months and the median overall survival was 16.8 (95% CI [13.3–27.7]) months. Three patients had in-field failure, five had out-field failure and two had in-field and out-field failure. Conclusion WBRT plus SIB led to improved tumor control and clinical outcome in breast cancer patients with brain metastasis.
Keywords: Breast cancer; Brain metastasis; WBRT; Simultaneous integrated boost; Outcome